On generalized Euler constants - Stankus, Eugenijus (Lietuvos matematikos rinkinys, 2002)
The generalized Euler constants are defined by formulasγ(r, k) = limx → ∞ {∑0 < n ≤  x; n ≡  r(mod k) ⅟n - ⅟k log x}.The explicit formula for γ(r, k) is obtained applying the method of contour integration.